FUNCTIONAL TRAINING APPLIED TO PERIODIZATION (Fiep Bulletin - online, 2016)
Functional training programs can assist in reducing disability, falls, emotional and social problems for practitioners of Functional Training. The aim of the study was to verify the methods of a functional exercise program practitioners in the functional training, assessing the impact on instrumental activities of daily living (IADL) and unipodálico balance. This quasi-experimental study attended seven community of practitioners (21 ± 8.1 years), without distinction of race and / or social status, excluding those with cognitive disorders, diseases Sharpened or neurological, painful condition of the spine or joints, labyrinthitis, non-compensated visual disturbances, previous fracture last year and use of support for the march. All responded to the questionnaire and Lawton underwent one leg stance test before and after the program, administered three times a week. The program consisted in running exercises in flexion plant, dorsiflexion, keeping in alternating one leg stance, gait Side with increased tandem gait and hip flexion. The results indicate improvement (p = 0.042) at the functional level (Lawton index) after the program and a trend towards improvement in unipodálico balance, although non-significant (p> 0.105). The proposed exercise program produced for improved performance AIVD and a trend towards improvement of static balance, suggesting that relevant to improve the autonomy of the elderly.
Keywords: Activities of daily living; Postural balance; functional training